Pengaruh Personal Characteristic, Work characteristic dan Work Experience terhadap Individual Commitment : Toxic Environment - Irawan, M. Deny; Pujianto, Wahyu Eko (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This study aims to test and analyse the effect of personal characteristics, job characteristics, work experience through on individual commitment by moderating the toxic environment in CV. Makmur Jaya employees. This research uses a quantitative descriptive approach. This research is quantitative in nature. The sampling technique used Purposive Sampling with a sample size of 45 employees. The statistical analysis used in this research is Partial Least Squares 4.1 (PLS). The results of this study indicate that: (1) there is a positive but insignificant effect of personal characteristics on individual commitment, (2) there is a positive and significant effect of job characteristics on individual commitment (3) there is a significant positive effect of work experience on individual commitment, (4) there is a negative and insignificant effect of toxic environment on individual commitment (5) there is a positive and insignificant effect of toxic environment weakening personal characteristics on individual commitment (6) there is a positive and significant effect of toxic environment weakening job characteristics on individual commitment and (7) there is a positive and insignificant effect of toxic environment weakening work experience on individual commitment.